Influencia de la dispersión atmosférica e instrumental en la distribución de brillo de una galaxia - Sérsic, José Luis (1963)
It is demonstrated that a generalized de Vaucouleurs law of brightness distribution is conserved after a smearing of gaussian profile at least in the first approximation.